HOW TO CREATE SOCIAL COHESION DURING PANDEMIC? A SOCIOLOGICAL ANALYSIS OF DIGITAL VOLUNTARISM AS THE PATH OF THE RECONSTRUCTION OF RELIGIOUS CONSCIOUSNESS IN INDONESIA - Andri Azis Putra (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
The most important function of religious rituals is to accept the expression of shared values and goals in society. This function combines social awareness with patterns of interaction in creating solidarity. Currently, social distancing has been seen by many Indonesians as the cause of the degradation of the value of spiritual intimacy in religious rituals. Meanwhile, the need to accept the “New Normal” in all aspects of daily life is absolute for citizens. Therefore, a new conception of this claim is certainly needed to accommodate the pressure in the adaptation process to the